La contribución del feedback en el proceso de evaluación formativa - Cremilde Mendes dos Santos; Renata Fischer da Silveira Kroeff (Universidade Federal de Rondônia, 2018)
The most recent studies about formative evaluation show that the use of effective feedback in this evaluative modality functions as an efficient strategy of motivation and regulation of learning, leading to autonomy and the development of competences on the part of the student. The purpose of this work is to investigate the importance of feedback in the evaluation in general and also its application in the field of Continuing Education in Health. For this, a Narrative Review of Literature was used as methodological strategy, searching for publications that deal with the theme Feedback in the context of formative evaluation. Eight studies pertinent to the chosen theme were selected. We present an analysis of the definitions and strategies of evaluation feedback found and discuss their possible contributions to the Continuing Education in Health.